Kompensasi Dalam Ekonomi Islam - Oktasari, Orin; Capriyanti, Orisa; Yolanda, Agnes; Suryani, Mardian; Khairunnisa, Arista (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Compensation in Islamic Economics, Compensation is the basic, or minimum, wage/salary and any additional payments paid directly or indirectly, whether in cash or in kind, by employers to workers in connection with the employment relationship. Compensation has an important role in the welfare of employees in a company/organization. Providing compensation to employees needs special attention from the organization/company in order to motivate employees and persist in working in the organization or company, because this is the area where there are many gaps in the implementation of compensation. For example, the minimum wage has not been realized, there is no social and health security. Islam explains that compensation must be given to employees as a reward that has been promised by employers, employers will get the results of work that has been completed while workers will get wages or compensation for the energy they have expended, then there is no gender difference in receiving wages/ reward from Allah. This concept of justice in wages dominates every practice that has ever occurred in Islamic countries. The basic principle used by the Prophet and Khulafaur Rasyidin was middle, moderate in determining employee wages, not too much or too little (proportional). The main purpose of providing wages is so that employees meet all their basic life needs. So, they are not encouraged to take actions that are not justified just to provide for themselves and their families (not corruption), therefore workers are required to get wages or compensation for the energy they have expended fairly and appropriately. Keywords: compensation, Islamic economics